2004
DOI: 10.1124/mol.104.002931
|View full text |Cite
|
Sign up to set email alerts
|

Tyr702 Is an Important Determinant of Agonist Binding and Domain Closure of the Ligand-Binding Core of GluR2

Abstract: Ionotropic glutamate receptors mediate most rapid excitatory synaptic transmission in the mammalian central nervous system, and their involvement in neurological diseases has stimulated widespread interest in their structure and function. Despite a large number of agonists developed so far, few display selectivity among (S)-2-amino-3-(3-hydroxy-5-methylisoxazol-4-yl) propionic acid (AMPA)-receptor subtypes. The present study provides X-ray structures of the glutamate receptor 2 (GluR2)-selective partial agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 40 publications
7
60
1
Order By: Relevance
“…Furthermore, there is a direct correlation between the degree of domain closure with full and partial AMPA receptor agonists and the degree of desensitization produced by those agonists Frandsen et al, 2005). Thus, the degree of agonist-induced LBD closure seems to be the primary determinant of tension at the LBD dimer interface and thus governs transition into both the open and desensitized state.…”
Section: Glutamate Receptor Ion Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is a direct correlation between the degree of domain closure with full and partial AMPA receptor agonists and the degree of desensitization produced by those agonists Frandsen et al, 2005). Thus, the degree of agonist-induced LBD closure seems to be the primary determinant of tension at the LBD dimer interface and thus governs transition into both the open and desensitized state.…”
Section: Glutamate Receptor Ion Channelsmentioning
confidence: 99%
“…Br-HIBO, an analog of ibotenic acid, preferentially activates GluA1 and GluA2 versus GluA3 and GluA4 receptors (Coquelle et al, 2000) through involvement of water-mediated hydrogen bonding to Tyr702 in GluA1 and GluA2, which is Phe in GluA3 and GluA4. Thus, ordered water molecules within the agonist binding site interact with the ligand to influence specificities among GluA subunits Hogner et al, 2002;Pentikä inen et al, 2003;Frandsen et al, 2005). Cl-HIBO was synthesized after molecular modeling predicted that the exchange of bromine for chlorine would improve selectivity (Bjerrum et al, 2003).…”
Section: Schiffer Et Al (1997)mentioning
confidence: 99%
“…4 The ligand-binding site is situated in a cleft between two domains, D1 and D2, which can move as rigid bodies independent of each other (i.e., as a clamshell-like structure), and agonist efficacy has been shown to correlate to the degree of domain closure upon agonist binding. 9,10 Together with functional data of full-length iGluRs, the crystal structures form the basis of a well-established model of AMPA receptor activation and desensitization. 4,9,11,12 Desensitization characteristics of iGluRs can be positively modulated by small allosteric modulators, ions, and plant lectins.…”
Section: Introductionmentioning
confidence: 99%
“…We would anticipate that such ligands would be even weaker agonists that kainate. The behavior of water surrounding subsite D principally reflects a key water identified in a series of crystallographic studies (Armstrong and Gouaux, 2000) and more recently has been suggested to play a central role in GluR1/GluR2 versus GluR3/GluR4 selectivity (Hogner et al, 2002;Frandsen et al, 2005).…”
Section: Figmentioning
confidence: 99%